Optimalisasi Biaya Transportasi Pekerja Bagian kurir pada PT. Indah Shipping Cabang Samarinda - Heriyanto 3, Muhammad Mashuri1 LCA Robin Jonathan2 (EKONOMIA, 2021)
The purpose of this study was to determine the part of workers courier transportation costs at PT. Indah Shipping Branch Samarinda for optimality. The theory used in this research is the Operational Management, Services, Transportation Linear Programming and Optimization. The research was conducted at PT. Indah Shipping Branch Samarinda. Data obtained secondary data and premiere in the can with the permission of the company that is the cost of fuel oil and other auxiliary costs. To obtain optimal transport costs by using the assignment method that produces the effectiveness and efficiency of each source to each destination. This research analysis tools using Hungarian method is modifying rows and columns of the matrix effective to turn up a single zero component of each row and column can be selected as the optimal allocation of assignments. The results of this study indicate assignments by using Hungarian method can yield an optimal solution that is more efficient compared with using existing assignment at. PT. Indah Shipping Branch Samarinda, There seems to be happening as much efficiency after using Hungarian method.